2021
DOI: 10.1167/iovs.62.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Early Astigmatism Can Alter Myopia Development in Chickens

Abstract: Purpose To determine the effects of optically imposed astigmatism on myopia development in chickens. Methods Chicks were randomly assigned to wear either spherical (−10D, “LIM”, n = 14) or sphero-cylindrical lenses ( n ≥ 19 in each group) monocularly for a week from 5 days of age. All lenses imposed the same magnitude of spherical-equivalent hyperopic defocus (−10D), with the two astigmatic magnitudes (−8D or −4D) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 61 publications
1
17
1
Order By: Relevance
“…When mfERG responses were compared across three time points in a group of chicks made myopic by full-field form deprivation, noticeable timing differences in mfERG waveform were also noted 16 . It should be noted that in addition to an elongated eyeball in our sphero-cylindrical lens treated chicks, they also developed a significantly higher magnitude of astigmatism compared to -10D lens (in particular the WTR treated group, Table 1 ), in agreement with the refractive and axial changes using sphero-cylindrical lenses with different magnitudes and axes in a separate study 17 . Because earlier studies usually used spherical equivalent to represent refractive change and changes in J0 and J45 astigmatic components were not available, it is difficult to directly compare the results between Schmid et al (2013) with the current study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When mfERG responses were compared across three time points in a group of chicks made myopic by full-field form deprivation, noticeable timing differences in mfERG waveform were also noted 16 . It should be noted that in addition to an elongated eyeball in our sphero-cylindrical lens treated chicks, they also developed a significantly higher magnitude of astigmatism compared to -10D lens (in particular the WTR treated group, Table 1 ), in agreement with the refractive and axial changes using sphero-cylindrical lenses with different magnitudes and axes in a separate study 17 . Because earlier studies usually used spherical equivalent to represent refractive change and changes in J0 and J45 astigmatic components were not available, it is difficult to directly compare the results between Schmid et al (2013) with the current study.…”
Section: Discussionsupporting
confidence: 79%
“…Using sphero-cylindrical lenses to impose hyperopic astigmatism, which is commonly found in the clinic, we recently reported the differential effects of astigmatic subtypes on myopia progression 17 . In the current study, it was investigated whether and how induced myopic-astigmatism influenced retinal functions, using a global flash mfERG protocol, assisted by a confocal scanning laser ophthalmoscope (cSLO).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in animal studies, the orientation of the imposed astigmatism is a factor influencing the magnitude of compensation, but the induced astigmatism in chicks was higher when rearing with WTR than with ATR astigmatic defocus, which is opposite to the trend observed in the current study. 25 27 However, it should be noted that the J0 astigmatism compensation, in terms of magnitude, was not significantly different between the two astigmatism conditions (Paired t -test, paired t (18) = 0.720, P = 0.481), so the effect of orientation on the rate of compensation cannot be concluded in the current study. To date, only one study has reported short-term, posterior anatomic change in human eyes after participants were exposed to monocular astigmatic blurs for 60 minutes.…”
Section: Discussioncontrasting
confidence: 57%
“…Nevertheless, the contribution of internal astigmatism, mainly originating from the crystalline lenses and partially from the posterior corneal toricity, should not be neglected. The disappearance of infantile astigmatism in human eyes 8 and refractive astigmatism development reported in animal eyes 26 , 27 were both shown to be accompanied by changes in corneal and internal astigmatism, suggesting the involvement of the cornea and crystalline lenses in astigmatism compensation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation